PD-L1 regulation by SDH5 via β-catenin/ZEB1 signaling. (2nd December 2019) - Tuo, Zhan; Zong, Yan; Li, Jie; Xiao, Guangqin; Zhang, Furong; Li, Guiling; Wang, Sihua; Lv, Yi; Xia, Jiahong; Liu, Jun
ABSTRACT: Programmed death-ligand 1 (PD-L1) is a crucial target for lung cancer immunotherapy. In lung cancer patients with high PD-L1 expression, blocking or reducing its expression can inhibit tumor growth. PD-L1 is regulated by signaling pathways, transcription factors and epigenetic factors, such as the GSK3β/β-catenin pathway, P53 protein and EMT. In our previous study, succinate dehydrogenase 5 ( SDH5 ) was reported to regulate ZEB1 expression, induce EMT and lead to lung cancer metastasis via the GSK3β/β-catenin pathway. It is possible that SDH5 is involved in the mechanisms of PD-L1 regulation.In the present study, we observed a negative correlation between the expression of PD-L1 and SDH5 in vivo and in vitro. The examination of patient tissues also confirmed our results. Furthermore, we also found that SDH5 could reverse PD-L1 expression by the GSK3β/β-catenin/ZEB1 pathways. All these results reveal that SDH5 regulates PD-L1 expression and suggest that SDH5 can be used as a marker to predict tumor immune micro-states and provide guidance for clinical immunotherapy.